Biological and physico-mechanical properties of poly(methyl methacrylate) enriched with graphene oxide as a potential biomaterial - René García-Contreras; Héctor Guzmán-Juárez; Daniel López-Ramos; Carlos Alvarez-Gayosso (Journal of Oral Research, 2021)
Objective: To determine the cytotoxicity and effects of graphene oxide (GO) on cellular proliferation of gingival-fibroblasts, pulpdental cells and human osteoblasts in culture, and to determine the physical, mechanical and biological properties of poly (methyl methacrylate) (PMMA) enriched with GO. Material and Methods: T he G O w as c haracterized with SEM. Cytotoxicity and cell proliferation were determined by the MTT bioassay. The physical-mechanical tests (flexural strength and elastic modulus) were carried out with a universal testing machine. Sorption and solubility were determined by weighing before and after drying and immersion in water. Porosity was evaluated by visual inspection. Data were analyzed with Student's t-test and Tukey's post-hoc ANOVA. Results: The GO has a heterogeneous morphology and a particle size of 66.67±64.76 μm. GO has a slight to no-cytotoxicity (>50-75% viability) at 1-30 days, and at 24 hours incubation of PMMA with GO significantly stimulates osteoblasts (45±8%, p<0.01). The physical and mechanical properties of PMMA with GO increase considerably without altering sorption, solubility and porosity. Conclusion: GO alone or with PMMA has an acceptable biocompatibility, could contribute to cell proliferation, cell regeneration and improve the physical-mechanical properties of PMMA.